2017
DOI: 10.1371/journal.ppat.1006603
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax edema toxin disrupts distinct steps in Rab11-dependent junctional transport

Abstract: Various bacterial toxins circumvent host defenses through overproduction of cAMP. In a previous study, we showed that edema factor (EF), an adenylate cyclase from Bacillus anthracis, disrupts endocytic recycling mediated by the small GTPase Rab11. As a result, cargo proteins such as cadherins fail to reach inter-cellular junctions. In the present study, we provide further mechanistic dissection of Rab11 inhibition by EF using a combination of Drosophila and mammalian systems. EF blocks Rab11 trafficking after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 67 publications
(108 reference statements)
1
19
0
Order By: Relevance
“…The approaches used and overall findings with CT were similar to those with ET (Guichard et al, 2010;Guichard et al, 2013;Guichard et al, 2017) Similar to the situation observed with ET, CT was found to affect the barrier function of host cells, in part, through the cAMP effector EPAC (Guichard et al, 2013). Specifically, the effect of CT on the structure of TJs in Caco-2 cells was reversed by treatment with a chemical inhibitor of EPAC.…”
Section: Cholera Toxinsupporting
confidence: 59%
See 1 more Smart Citation
“…The approaches used and overall findings with CT were similar to those with ET (Guichard et al, 2010;Guichard et al, 2013;Guichard et al, 2017) Similar to the situation observed with ET, CT was found to affect the barrier function of host cells, in part, through the cAMP effector EPAC (Guichard et al, 2013). Specifically, the effect of CT on the structure of TJs in Caco-2 cells was reversed by treatment with a chemical inhibitor of EPAC.…”
Section: Cholera Toxinsupporting
confidence: 59%
“…The approaches used and overall findings with CT were similar to those with ET (Guichard et al, ; Guichard et al, ; Guichard et al, ). Ectopic expression of CtxA in Drosophila wings caused a Notch phenotype and also inhibited localisation of Delta, Rab11, Sec15, and DE‐cadherin to AJs.…”
Section: Exocytosis and Microbial Pathogenesismentioning
confidence: 61%
“…We therefore wondered whether EF might also block the effects of CDTa. Alone, EF expression causes wing phenotypes consisting of blistered wings with thickened veins and notched margins ( Figure S2A, and Guichard et al, 2017;Guichard et al, 2006). Consistent with its inhibitory activity on Rab11, EF partially suppressed the CDTa wing phenotype, leading to an enlarged and partially restored wing blade ( Figure S2A, quantified in S2B).…”
Section: Anthrax Toxin Ef Partially Rescues Cdta-induced Phenotypesmentioning
confidence: 60%
“…We previously reported that the anthrax toxin Edema Factor (EF), a potent Adenylate Cyclase, inhibits Rab11 activity, leading to junctional defects (Guichard et al, 2017). We therefore wondered whether EF might also block the effects of CDTa.…”
Section: Anthrax Toxin Ef Partially Rescues Cdta-induced Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation